CO08 | The utility of urine qualitative assessment for direct oral anticoagulants in routine clinical practice (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Direct Oral Anticoagulants (DOACs) are increasingly prescribed in clinical practice because of their predictable pharmacokinetic and pharmacodynamic profiles. However, measuring DOAC levels can be relevant in some conditions, such as suspicion of drug-drug interaction, extreme body weight, treatment failure, liver or renal insufficiency. In this regard, some information is available with plasma measurement of DOACs, while there is still a significant gap in knowledge concerning qualitative urinary testing. In this study we want to evaluate the reliability of qualitative urinary detection by DOASENSE Dipstick (Harenberg et al, TH 2024) compared to the corresponding plasma testing of anti-Xa and anti-IIa anticoagulant drugs in patients enrolled in an ambulatory setting.